2009
DOI: 10.1128/aem.00902-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutations That Disrupt Either thepqqor thegdhGene ofRahnella aquatilisAbolish the Production of an Antibacterial Substance and Result in Reduced Biological Control of Grapevine Crown Gall

Abstract: Rahnella aquatilis HX2, a biocontrol agent for grapevine crown gall caused by Agrobacterium vitis, produces an antibacterial substance that inhibits the growth of A. vitis in vitro. In this study, we show that MH15 and MH16, two Tn5-induced mutants of HX2, have lost their abilities to inhibit A. vitis and have reduced biocontrol activities; they grow in logarithmic phase at a rate similar to that of the wild type and have single Tn5 insertions. They are also impaired in producing pyrroloquinoline quinone (PQQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 56 publications
(63 reference statements)
1
43
0
1
Order By: Relevance
“…Five bacteria with demonstrated PQQ biosynthetic capacity were selected for this study: Klebsiella pneumoniae , Methylobacterium extorquens AM1 , Gluconobacter oxydans 621H , Rahnella aquatilis and Streptomyces rochei (1923). Each of the genes in the pqq operons in these five bacteria (shown in Table 1) was used as starting points for bioinformatics analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Five bacteria with demonstrated PQQ biosynthetic capacity were selected for this study: Klebsiella pneumoniae , Methylobacterium extorquens AM1 , Gluconobacter oxydans 621H , Rahnella aquatilis and Streptomyces rochei (1923). Each of the genes in the pqq operons in these five bacteria (shown in Table 1) was used as starting points for bioinformatics analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation of glucose to gluconic acid is catalysed by membrane-bound quinoprotein glucose dehydrogenases (Gcd) that are involved either in biocontrol of plant pathogens [10], [13] or in pathogenicity of bacteria in mammals [14]. Among various quinoprotein dehydrogenase enzymes in bacteria, Gcd uses pyrroloquinoline quinone (PQQ) as an essential cofactor [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with bacterial mutants unable to produce PQQ and gluconic acid have demonstrated the intimate relation of the cofactor to phosphate solubilization processes (7,17). Besides its relevant role in P solubilization, PQQ is reported to be a potent growth-promoting factor for bacteria and plants, has antioxidant properties (5), and is directly related to the production of antimicrobial substances (7,14,36) as well as to the induction of systemic plant defenses (17). Hence, the cofactor PQQ has multiple plant beneficial effects.…”
mentioning
confidence: 99%
“…The genes responsible for PQQ production have been cloned and sequenced in several bacterial genera, including Pseudomonas, Methylobacterium, Acinetobacter, Klebsiella, Enterobacter, and Rahnella (5,14,17,36,42). In P. fluorescens B16, the PQQ operon is formed by 11 …”
mentioning
confidence: 99%